Polysilazane composite coating as well as preparation method and application thereof

By adding toughener, lubricant and two-dimensional composite filler to the polysilazane coating, the problem of high brittleness of the polysilazane coating is solved, its wear resistance and corrosion resistance are improved, and marine engineering is realized Efficient protection of transmission system components.

CN119220177APending Publication Date: 2024-12-31YANTAI ZHONGKE RES INST OF ADVANCED MATERIALS & GREEN CHEM ENG +1

Patent Information

Application Number
CN202411489129.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing polysilazane coating is highly brittle and prone to cracking, making it difficult to meet the demand for high reliability and long-life operation of marine engineering equipment transmission system components.

Method used

Using polysilazane composite coatings, toughening agents such as elastic polymers, lubricants such as alcohols and esters, as well as two-dimensional composite fillers and additives, the coating is prepared by mixing and in-situ growth methods to improve the coating. wear resistance, corrosion resistance and lubricity.

Benefits of technology

The hardness, wear resistance and corrosion resistance of the polysilazane composite coating are improved, and cracking problems are avoided, so that the coating can be coated thickly and provides good protective effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005099511060000121
    Figure BDA0005099511060000121
Patent Text Reader

Abstract

The invention belongs to the technical field of protective coatings, and provides a polysilazane composite coating as well as a preparation method and application thereof. According to the polysilazane composite coating disclosed by the invention, the elastic polymer is used as a toughening agent, so that the toughening effect on polysilazane can be achieved, and the problem of high brittleness of polysilazane is solved; and by using the flexibilizer, the internal stress of the polysilazane composite coating formed by the polysilazane composite coating can be reduced, and the cracking of the polysilazane composite coating is avoided, so that the polysilazane composite coating can be thickly coated. Alcohol substances and / or ester substances are used as the lubricant, so that the lubricity and wear resistance of the polysilazane composite coating formed by the polysilazane composite coating can be improved. And by using the two-dimensional composite material, the wear resistance and corrosion resistance of the polysilazane composite coating formed by the polysilazane composite coating can be obviously improved, and meanwhile, the polysilazane composite coating can be endowed with a lubricating function.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of protective coatings, and in particular to a polysilazane composite coating and a preparation method and application thereof. Background Art

[0002] In recent years, high-end technical equipment independently developed by my country has gradually entered the stage of mass service. However, the mechanical motion system components of these equipment are directly exposed to the marine atmosphere. The chemical and electrochemical corrosion caused by the marine atmosphere and the friction and wear caused by mechanical factors interact, which greatly accelerates the damage and failure of metal materials. Current marine engineering materials cannot fully meet the high reliability and long life operation requirements of the transmission systems / components exposed to the outside of marine equipment. Therefore, how to solve the synergistic damage of corrosion and wear faced by the motion system / transmission components in the marine salt spray atmosphere is a common technical problem that needs to be solved urgently in the field of marine engineering equipment.

[0003] Surface coating technology has the advantages of simple and feasible methods, low cost, and strong protection ability. It has become one of the effective methods to protect the surface of submarine equipment from biological contamination and corrosion and reduce friction and wear. As a low surface energy coating, polysilazane coating contains abundant Si-N-Si bonds, which are very easy to combine with -OH on the surface of the substrate, so it has good bonding force with the substrate. And the polysilazane coating has high hardness and good wear resistance after curing. In addition, the Si-H, Si-N, and NH bonds in polysilazane are very sensitive to water and oxygen, and the chemical reaction is relatively active, so it is easy to modify polysilazane. At present, polysilazane is widely used in cables, cookers, photovoltaic cells and other fields; however, when polysilazane is used, polysilazane coating is prepared with polysilazane as a single component, and the single polysilazane coating has the problem of high brittleness and easy cracking after curing. Summary of the invention

[0004] In view of this, the object of the present invention is to provide a polysilazane composite coating and a preparation method and application thereof. The polysilazane composite coating obtained after curing is less brittle and less prone to cracking, and the polysilazane composite coating can be applied thickly.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a polysilazane composite coating, which comprises the following components in parts by mass:

[0007] 5-15 parts of polysilazane, 1-5 parts of toughening agent, 1-5 parts of lubricant, 0.05-0.5 parts of two-dimensional composite filler, 10-30 parts of dispersion medium, 0.01-0.1 parts of auxiliary agent;

[0008] The toughening agent is an elastic polymer;

[0009] The lubricant is an alcohol substance and / or an ester substance.

[0010] Preferably, the polysilazane includes one or more of vinyl polysilazane, methyl polysilazane, polyurea silazane, fluorine-modified polysilazane, polyborosilazane and perhydropolysilazane.

[0011] Preferably, the elastic polymer includes one or more of nitrile rubber, hydroxyl-terminated polybutadiene rubber, chloroprene rubber, natural rubber, styrene-butadiene rubber, butadiene rubber, hydrogenated nitrile rubber, butyl rubber, thermoplastic polyurethane elastomer, acrylate rubber and isoprene rubber.

[0012] Preferably, the alcohol substance includes one or more of monohydric alcohol, dihydric alcohol, trihydric alcohol and tetrahydric alcohol, the monohydric alcohol includes one or more of dodecanol, 12-hydroxystearic acid, isomeric tridecanol, tetradecanol, hexadecanol and octadecyl alcohol, the dihydric alcohol includes one or more of ethylene glycol, propylene glycol, pentanediol, hexanediol and cis-2-butene-1,4-diol, the trihydric alcohol includes one or more of glycerol, butanetriol and estriol, and the tetrahydric alcohol includes pentaerythritol; the ester substance includes trimethylolpropane oleate and / or glyceryl trihydroxystearate.

[0013] Preferably, the two-dimensional composite filler comprises a two-dimensional sheet material and a nanomaterial attached to the surface of the two-dimensional sheet material; the nanomaterial comprises a metal oxide nanomaterial or a nanometal;

[0014] The two-dimensional sheet material includes one or more of graphene oxide, molybdenum disulfide, hexagonal boron nitride, mica sheet, MXene material and clay;

[0015] The metal oxide nanomaterial includes magnesium oxide, calcium oxide, aluminum oxide or zinc oxide;

[0016] The nano metal includes iron, copper, magnesium, cobalt or zinc;

[0017] The mass ratio of the two-dimensional sheet material to the nano material is 1:1 to 10:1.

[0018] Preferably, the dispersion medium includes one or more of n-butyl ether, n-hexane, propylene glycol methyl ether acetate, acetone, dichloromethane, ethyl acetate, tetrahydrofuran, 1,1,2-trichlorotrifluoroethane, perfluorohexane, perfluorocyclohexane, perfluorotoluene, perfluoroheptane and perfluorotrialkylamine.

[0019] Preferably, the auxiliary agent includes a wetting and dispersing agent, a defoaming agent, a leveling agent and a dustproof agent; the mass ratio of the wetting and dispersing agent, the defoaming agent, the leveling agent and the dustproof agent is (0.9-1.1): (1.0-1.2): (0.8-1.0): (0.8-1.0).

[0020] The present invention also provides a method for preparing the polysilazane composite coating described in the above technical solution, comprising the following steps:

[0021] The polysilazane, the toughening agent, the lubricant and the dispersion medium are first mixed to obtain a first mixed slurry;

[0022] The first mixed slurry and the two-dimensional composite filler are mixed for a second time to obtain a second mixed slurry;

[0023] The second mixed slurry and the auxiliary agent are mixed for the third time to obtain the polysilazane composite coating.

[0024] The present invention also provides the use of the polysilazane composite coating described in the above technical solution or the polysilazane composite coating prepared by the preparation method described in the above technical solution in the protection of metal substrates.

[0025] Preferably, the coating thickness of the polysilazane composite coating is 5 to 100 μm.

[0026] The invention provides a polysilazane composite coating.

[0027] In the present invention, the polysilazane in the polysilazane composite coating contains abundant Si-N-Si bonds, which are very easy to combine with -OH on the surface of the substrate, and thus have good bonding force with the substrate; and, the presence of polysilazane makes the polysilazane composite coating solidify, and the obtained polysilazane composite coating has high hardness and good wear resistance. The present invention uses an elastic polymer as a toughening agent, which can play a toughening effect on polysilazane, solving the problem of large brittleness of polysilazane; the use of a toughening agent can also reduce the internal stress of the polysilazane composite coating formed by the polysilazane composite coating, avoid the cracking of the polysilazane composite coating, and then enable the polysilazane composite coating to be thickly coated. With alcohols and / or esters as lubricants, the lubricity and wear resistance of the polysilazane composite coating formed by the polysilazane composite coating can be improved. The use of two-dimensional composite materials can also significantly improve the wear resistance and corrosion resistance of the polysilazane composite coating formed by the polysilazane composite coating, and can also give the polysilazane composite coating lubrication function. The additive firstly ensures that the two-dimensional composite material is evenly dispersed in the polysilazane composite coating, so that the polysilazane composite coating is not easy to settle; secondly, the additive enables the polysilazane composite coating to have good wetting and leveling properties on the surface of the substrate; in addition, the additive can also make the polysilazane composite coating formed by the polysilazane composite coating dense, free of bubbles, nodules and other defects. DETAILED DESCRIPTION

[0028] The present invention provides a polysilazane composite coating, which comprises the following components in parts by mass:

[0029] 5-15 parts of polysilazane, 1-5 parts of toughening agent, 1-5 parts of lubricant, 0.05-0.5 parts of two-dimensional composite filler, 10-30 parts of dispersion medium, 0.01-0.1 parts of auxiliary agent;

[0030] The toughening agent is an elastic polymer;

[0031] The lubricant is an alcohol substance and / or an ester substance.

[0032] In the present invention, unless otherwise specified, the raw materials used in the present invention are preferably commercially available products.

[0033] The polysilazane composite coating provided by the present invention includes 5 to 15 parts by mass of polysilazane, specifically 5 parts, 10 parts or 15 parts. In the present invention, the polysilazane preferably includes one or more of vinyl polysilazane, methyl polysilazane, polyurea silazane, fluorine-modified polysilazane, polyborosilazane and perhydropolysilazane. In the present invention, the polysilazane can react with an organic compound having an active functional group at the molecular level, and then develop into a coating with both multifunctionality; at the same time, polysilazane contains abundant Si-N-Si bonds, which are very easy to combine with -OH on the surface of the substrate, and thus have good bonding force with the substrate; in addition, the presence of polysilazane makes the polysilazane composite coating have high hardness and good wear resistance after curing.

[0034] The polysilazane composite coating provided by the present invention includes a toughening agent of 1 to 5 parts by mass, which can be specifically 1 part, 2 parts, 3 parts, 4 parts or 5 parts. In the present invention, the toughening agent is an elastic polymer, and the elastic polymer preferably includes one or more of nitrile rubber, hydroxyl-terminated polybutadiene rubber, chloroprene rubber, natural rubber, styrene-butadiene rubber, butadiene rubber, hydrogenated nitrile rubber, butyl rubber, thermoplastic polyurethane elastomer, acrylate rubber and isoprene rubber. The present invention uses an elastic polymer as a toughening agent, which can have a toughening effect on polysilazane and solve the problem of large brittleness of polysilazane; the use of a toughening agent can also reduce the internal stress of the polysilazane composite coating formed by the polysilazane composite coating, avoid cracking of the polysilazane composite coating, and thus enable the polysilazane composite coating to be thickly coated.

[0035] The polysilazane composite coating provided by the present invention includes a lubricant of 1 to 5 parts by mass, specifically 1 part, 2 parts, 3 parts, 4 parts or 5 parts. In the present invention, the lubricant is an alcohol substance and / or an ester substance. In the present invention, the alcohol substance preferably includes one or more of a monohydric alcohol, a dihydric alcohol, a trihydric alcohol and a tetrahydric alcohol, and the monohydric alcohol preferably includes one or more of dodecanol, 12-hydroxystearic acid, isomeric tridecanol, tetradecanol, hexadecanol and octadecyl alcohol; the dihydric alcohol preferably includes one or more of ethylene glycol, propylene glycol, pentanediol, hexanediol and cis-2-butene-1,4-diol; the trihydric alcohol preferably includes one or more of glycerol, butanetriol and estriol, and the tetrahydric alcohol preferably includes pentaerythritol. In the present invention, the ester substance preferably includes trimethylolpropane oleate and / or glyceryl trihydroxystearate. In the present invention, alcohol substances and / or ester substances are used as lubricants to improve the lubricity and wear resistance of the polysilazane composite coating formed by the polysilazane composite coating.

[0036] The polysilazane composite coating provided by the present invention includes 0.05 to 0.5 parts by mass of a two-dimensional composite filler, specifically 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45 or 0.5 parts. In the present invention, the two-dimensional composite filler preferably includes a two-dimensional sheet material and a nanomaterial attached to the surface of the two-dimensional sheet material; the nanomaterial preferably includes a metal oxide nanomaterial or a nanometal. In the present invention, the two-dimensional sheet material preferably includes one or more of graphene oxide, molybdenum disulfide, hexagonal boron nitride, mica flakes, MXene materials and clay, more preferably graphene oxide; the sheet diameter of the two-dimensional sheet material is preferably 1000 to 10000 nm, more preferably 1000 to 8000 nm, specifically 3000 to 5000 nm. In the present invention, the metal oxide nanomaterial preferably includes magnesium oxide, calcium oxide, aluminum oxide, zinc oxide or copper oxide; the shape of the metal oxide nanomaterial is preferably flaky, and the flake diameter of the metal oxide nanomaterial is 100 to 1000 nm, more preferably 200 to 800 nm; in the present invention, the nanometal preferably includes iron, copper, magnesium, cobalt or zinc, more preferably magnesium, cobalt or zinc; the shape of the nanometal is preferably flaky or granular, more preferably flaky, and the flake diameter or particle diameter of the nanometal is preferably 50 to 500 nm, more preferably 60 to 300 nm. In the present invention, the mass ratio of the two-dimensional sheet material and the nanomaterial is preferably 1:1 to 10:1.

[0037] In the present invention, the method for preparing the two-dimensional composite filler preferably comprises the following steps:

[0038] The two-dimensional sheet material, the nanomaterial precursor solution and the solvent are mixed to obtain a dispersion;

[0039] When the nanomaterial is a metal oxide, the nanomaterial precursor solution is a first soluble metal salt solution; the dispersion and the alkaline solution are mixed to perform a first in-situ growth and then calcined under nitrogen protection to obtain the two-dimensional composite material;

[0040] When the nanomaterial is nanometal, the nanomaterial precursor solution is a second soluble metal salt solution; the dispersion, solvent, dispersant and surfactant are mixed for second in-situ growth and then calcined under nitrogen protection to obtain the two-dimensional composite material.

[0041] The invention mixes the two-dimensional sheet material, the nano material precursor solvent and the solvent to obtain a dispersion.

[0042] In the present invention, the mixing preferably includes the following steps: dispersing the two-dimensional sheet material in a solvent to obtain a first dispersion; first mixing the first dispersion and the nanomaterial precursor solution. In the present invention, the solvent is preferably water; the water is preferably deionized water. The present invention has no special restrictions on the amount of the solvent, as long as the two-dimensional sheet material can be evenly dispersed. In the present invention, the dispersion is preferably carried out under ultrasonic conditions. The present invention has no special restrictions on the power and time of the ultrasound, as long as it can be evenly dispersed.

[0043] In the present invention, when the nanomaterial is a metal oxide, the nanomaterial precursor solution is a first soluble metal salt; the soluble metal salt in the first soluble metal salt is preferably magnesium sulfate, magnesium nitrate hexahydrate, aluminum nitrate, calcium methanolate, zinc nitrate hexahydrate, zinc acetate dihydrate or copper nitrate trihydrate, more preferably magnesium nitrate hexahydrate, copper nitrate trihydrate or zinc acetate dihydrate.

[0044] In the present invention, when the nanomaterial is a nanometal, the nanomaterial precursor solution is a second soluble metal salt solution; the soluble metal salt in the second soluble metal salt solution is preferably magnesium chloride, zinc chloride, copper chloride dihydrate, ferric chloride hexahydrate or cobalt chloride hexahydrate, more preferably magnesium chloride or zinc chloride. In the present invention, the soluble metal salt is preferably a powder.

[0045] In the present invention, the first mixing is preferably carried out under stirring conditions. The present invention has no special requirements on the speed and time of the stirring, as long as the mixing is uniform.

[0046] After obtaining the dispersion, when the nanomaterial is a metal oxide, the present invention mixes the dispersion with an alkaline solution to perform a first in-situ growth and then calcines under nitrogen protection to obtain the two-dimensional composite material.

[0047] In the present invention, the alkaline solution preferably includes sodium hydroxide solution, potassium hydroxide solution or ammonia water, more preferably sodium hydroxide solution. In the present invention, the molar concentration of the alkaline solution is preferably 1-20 mol / L, more preferably 1-10 mol / L. In the present invention, the molar ratio of the nanomaterial precursor and the hydroxide ion in the alkaline solution is preferably 1:10-25, more preferably 1:10-15. In the present invention, the temperature of the first in-situ growth is preferably 80-250°C, more preferably 80-180°C; the time of the first in-situ growth is preferably 2-20h, more preferably 5-15h. The present invention regulates the morphology of the metal oxide by controlling the precursor type, solvent type, temperature and time of the first in-situ growth. In the present invention, after the first in-situ growth, it is preferably further included: cooling the system after the first in-situ growth to room temperature and then washing and drying in sequence. In the present invention, the temperature of the room temperature is preferably 20-35°C, more preferably 25-30°C. In the present invention, the cooling is preferably natural cooling. In the present invention, the washing preferably includes water washing and ethanol washing in sequence; the water used for the water washing is preferably deionized water, and the number of water washings is preferably 6 to 8 times, specifically 6 times, 7 times or 8 times; the ethanol used for the ethanol washing is preferably anhydrous ethanol, and the number of ethanol washings is preferably 4 to 8 times, specifically 4 times, 5 times, 6 times, 7 times or 8 times. In the present invention, the drying is preferably freeze drying. In the present invention, the calcination temperature is preferably 400 to 500°C, more preferably 450°C; the heating rate to the temperature required for the calcination is preferably 1 to 10°C / min, more preferably 5 to 8°C / min; the calcination holding time is preferably 3 to 5h, more preferably 4h. In the present invention, the metal ions in the metal oxide precursor in the dispersion and the hydroxide ions in the alkaline solution react during the first in-situ growth process to generate metal hydroxides attached to the surface of the two-dimensional sheet material; the metal hydroxides are converted into metal oxides after calcination. The heating rate of the calcination limited by the present invention can avoid the sudden collapse of the oxide structure during the calcination process.

[0048] After obtaining the dispersion, when the nanomaterial is nanometal, the present invention mixes the dispersion, solvent, dispersant and surfactant for second in-situ growth and then calcines under nitrogen protection to obtain the two-dimensional composite material.

[0049] In the present invention, the solvent is preferably ethylene glycol, the dispersant is preferably sodium acetate (NaAc), and the surfactant is preferably polyethylene glycol. In the present invention, the volume ratio of the dispersion and the solvent is preferably 1:1 to 5:1, specifically 1:1, 2:1, 3:1, 4:1 or 5:1. In the present invention, the mass ratio of the dispersant and the solvent is preferably 1:1 to 1:5, specifically 1:1, 1:2, 1:3, 1:4 or 1:5. In the present invention, the volume ratio of the surfactant and the solvent is preferably 1:1 to 5:1, specifically 1:1, 2:1, 3:1, 4:1 or 5:1. In the present invention, the temperature of the second in-situ growth is preferably 100 to 300°C, more preferably 150 to 250°C, specifically 100°C, 150°C, 200°C, 250°C or 300°C; the time of the second in-situ growth is preferably 1 to 48h, more preferably 1 to 16h. The present invention regulates the morphology of nanometal by controlling the precursor type, solvent type, temperature and time of the second in-situ growth. In the present invention, after the second in-situ growth, it is preferred that: the system after the second in-situ growth is cooled to room temperature and then filtered, washed and dried in sequence. In the present invention, the temperature of the room temperature is preferably 20-35°C, more preferably 25-30°C, specifically 20°C, 25°C, 30°C or 35°C. In the present invention, the cooling is preferably natural cooling. The present invention has no special requirements for the filtration, and the conventional method in the art can be used. In the present invention, the washing preferably includes water washing and ethanol washing in sequence; the water for the water washing is preferably deionized water, and the number of water washings is preferably 6-8 times, specifically 6 times, 7 times or 8 times; the ethanol for the ethanol washing is preferably anhydrous ethanol, and the number of ethanol washings is preferably 4-8 times, more preferably 5-7 times, specifically 4 times, 5 times, 6 times, 7 times or 8 times. In the present invention, the drying is preferably nitrogen-protected drying, the drying temperature is preferably 55-65°C, more preferably 60°C, specifically 55°C, 60°C or 65°C; the drying time is preferably 3-5h, more preferably 4h.

[0050] In the present invention, the use of the two-dimensional composite material can significantly improve the wear resistance and corrosion resistance of the polysilazane composite coating formed by the polysilazane composite coating, and can also give the polysilazane composite coating a lubricating function.

[0051] The polysilazane composite coating provided by the present invention comprises 10 to 30 parts by mass of a dispersion medium, specifically 10 parts, 15 parts, 20 parts, 25 parts or 30 parts. In the present invention, the dispersion medium preferably comprises one or more of n-butyl ether, n-hexane, propylene glycol methyl ether acetate, acetone, dichloromethane, ethyl acetate, tetrahydrofuran, 1,1,2-trichlorotrifluoroethane, perfluorohexane, perfluorocyclohexane, perfluorotoluene, perfluoroheptane and perfluorotrialkylamine.

[0052] The polysilazane composite coating provided by the present invention includes an auxiliary agent having a mass fraction of 0.01 to 0.1 parts, specifically 0.01 parts, 0.02 parts, 0.03 parts, 0.04 parts, 0.05 parts, 0.06 parts, 0.07 parts, 0.08 parts, 0.09 parts or 0.1 parts. In the present invention, the auxiliary agent preferably includes a wetting dispersant, a defoamer, a leveling agent and a dustproof agent. In the present invention, the mass ratio of the wetting dispersant, the defoamer, the leveling agent and the dustproof agent is preferably (0.9 to 1.1): (1.0 to 1.2): (0.8 to 1.0): (0.8 to 1.0), more preferably 1:1:1:1. In the present invention, the dispersant preferably includes one or more of Maier P1041, Maier HY-257, Enze 2513 and Lida LD-64200; the dispersant can improve the dispersibility of the two-dimensional composite filler in the polysilazane composite coating. In the present invention, the leveling agent preferably includes one or more of Maier HY-5030, Lida LD-91083 and Lida LD-9604; the leveling agent can reduce the surface tension between the polysilazane composite coating and the substrate, so that the polysilazane composite coating has good wettability with the substrate, and improves the fluidity of the polysilazane composite coating. In the present invention, the defoamer preferably includes one or more of Maier HY-037, Maier HY-62S, Enze B-100 and Lida LD-220; the defoamer can effectively eliminate bubbles in the coating and increase the density of the coating. In the present invention, the anti-settling agent preferably includes one or more of Lida LD-1291S, Yayu YB-201A and Yayu YB-401A, and more preferably one of Lida LD-1291S, Yayu YB-201A or Yayu YB-401A; the anti-settling agent can prevent the precipitation of the two-dimensional composite filler in the polysilazane composite coating and improve the stability of the polysilazane composite coating.

[0053] The present invention also provides a method for preparing the polysilazane composite coating described in the above technical solution, comprising the following steps:

[0054] The polysilazane, the toughening agent, the lubricant and the dispersion medium are first mixed to obtain a first mixed slurry;

[0055] The first mixed slurry and the two-dimensional composite filler are mixed for a second time to obtain a second mixed slurry;

[0056] The second mixed slurry and the auxiliary agent are mixed for the third time to obtain the polysilazane composite coating.

[0057] The present invention does not specifically limit the parameters of the first mixing, the second mixing and the third mixing, as long as the materials can be mixed uniformly.

[0058] The present invention also provides the use of the polysilazane composite coating described in the above technical solution or the polysilazane composite coating prepared by the preparation method described in the above technical solution in the protection of metal substrates.

[0059] In the present invention, the material of the metal substrate is preferably carbon steel, alloy steel, cast iron, tinplate, high temperature alloy, aluminum alloy, magnesium alloy or magnesium-lithium alloy.

[0060] In the present invention, the metal substrate is preferably subjected to sandblasting before being coated with the polysilazane composite coating, and the surface roughness of the metal substrate obtained after the sandblasting is preferably 0.5 to 4.0 μm, more preferably 1.0 to 3.0 μm. The present invention does not have any special restrictions on the conditions of the sandblasting, and the conditions well known to those skilled in the art can be used to ensure that the surface roughness of the metal substrate meets the above requirements.

[0061] In the present invention, the coating thickness of the polysilazane composite coating is preferably 5 to 100 μm.

[0062] In the present invention, after the polysilazane composite coating is applied, it also includes sequentially drying and curing. In the present invention, the temperature of the drying is preferably room temperature, and the time is preferably 6 to 8 hours. In the present invention, the curing temperature is preferably 60 to 180°C, more preferably 80 to 160°C, and most preferably 100 to 140°C; the time is preferably 1 to 6 hours, more preferably 2 to 4 hours.

[0063] The polysilazane composite coating provided by the present invention and its preparation method and application are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0064] Example 1

[0065] Weigh 5 g of methyl polysilazane, 1 g of terminal hydroxyl polybutadiene rubber, 2 g of 12-hydroxystearic acid, 1 g of trimethylolpropane oleate, and 1 g of glycerol trihydroxystearate, mix and disperse them in 10 g of n-butyl ether to obtain a first mixed slurry; add 0.1 g of a two-dimensional composite material (graphene oxide (sheet diameter is 3000-5000 nm) and magnesium oxide (lamellar morphology, sheet diameter is 200-300 nm) in a mass ratio of 1:1) to the first mixed slurry, stir well to obtain a second mixed slurry; add 0.02 g of Mayer HY-5030, 0.02 g of Enze 2513, 0.02 g of Mayer HY-62S and 0.02 g of Lida LD-1291S to the second mixed slurry, continue stirring for 10 minutes to obtain a polysilazane composite coating.

[0066] The metal substrate was sandblasted to achieve a surface roughness of 2.6 μm.

[0067] The polysilazane composite coating was uniformly sprayed on the surface of the metal substrate, and then surface dried for 6 hours at room temperature, and then cured at 120° C. for 2 hours to obtain a polysilazane composite coating.

[0068] The method for preparing the two-dimensional composite material comprises:

[0069] 0.1 g of two-dimensional sheet material graphene oxide was dispersed in 100 mL of deionized water under ultrasonic conditions to obtain a first dispersion.

[0070] The first dispersion liquid and 2.5 g of nanomaterial precursor Mg(NO3)2·6H2O were first mixed under stirring conditions to obtain a dispersion liquid.

[0071] The dispersion and sodium hydroxide solution (wherein the molar ratio of the nanomaterial precursor Mg(NO3)2·6H2O and the hydroxide ion in the sodium hydroxide solution is 1:15) are mixed and first grown in situ at 80°C for 2 hours and then cooled to 25°C. The obtained mixed solution is washed with deionized water 6 times and then with anhydrous ethanol 4 times. After washing, it is freeze-dried and subsequently calcined at 450°C under nitrogen protection for 4 hours to obtain a two-dimensional composite material.

[0072] Example 2

[0073] Weigh 5 g of vinyl polysilazane, 1 g of thermoplastic polyurethane elastomer and 1 g of trimethylolpropane oleate, mix and disperse them in 10 g of n-hexane to obtain a first mixed slurry; add 0.1 g of a two-dimensional composite material (graphene oxide (sheet diameter is 3000-5000 nm) and copper oxide (lamellar morphology, sheet diameter is 600-800 nm) in a mass ratio of 1:1) to the first mixed slurry, stir well to obtain a second mixed slurry, add 0.02 g of Mayer HY-5030, 0.02 g of Enze 2513, 0.02 g of Mayer HY-62S and 0.02 g of Lida LD-1291S to the second mixed slurry, continue stirring for 10 minutes, and obtain a polysilazane composite coating.

[0074] The metal substrate was sandblasted to achieve a surface roughness of 2.6 μm.

[0075] The polysilazane composite coating was uniformly sprayed on the surface of the metal substrate, and then surface dried for 6 hours at room temperature, and then cured at 120° C. for 2 hours to obtain a polysilazane composite coating.

[0076] Among them, the preparation methods of two-dimensional composite materials include:

[0077] Dispersing 0.1 g of two-dimensional sheet material graphene oxide in 100 mL of deionized water under ultrasonic conditions to obtain a first dispersion;

[0078] The first dispersion liquid and 2.5 g of nanomaterial precursor Cu(NO3)2·3H2O are first mixed under stirring conditions to obtain a dispersion liquid;

[0079] The dispersion and NaOH solution (wherein the molar ratio of the nanomaterial precursor Cu(NO3)2·3H2O and the hydroxide ions in the NaOH solution is 1:15) are mixed and first grown in situ at 180°C for 24 hours and then cooled to 25°C. The resulting mixed solution is washed with deionized water 6 times and then with anhydrous ethanol 4 times. The washed mixed solution is freeze-dried and then calcined at 450°C for 4 hours to obtain a two-dimensional composite material.

[0080] Example 3

[0081] Weigh 5 g of fluorine-modified polysilazane, 1 g of styrene-butadiene rubber and 1 g of glycerol trihydroxystearate, mix and disperse them in 10 g of ethyl acetate to obtain a first mixed slurry, add 0.1 g of a two-dimensional composite material (graphene oxide (sheet diameter is 3000-5000 nm) and zinc oxide (lamellar morphology, sheet diameter is 600-800 nm) in a mass ratio of 1:1) to the first mixed slurry, stir well to obtain a second mixed slurry; add 0.02 g of Mayer HY-5030, 0.02 g of Enze 2513, 0.02 g of Mayer HY-62S and 0.02 g of Lida LD-1291S to the second mixed slurry, continue stirring for 10 min to obtain a polysilazane composite coating.

[0082] The metal substrate was sandblasted to achieve a surface roughness of 2.6 μm.

[0083] The polysilazane composite coating was uniformly sprayed on the surface of the metal substrate, and then surface dried for 6 hours at room temperature, and then cured at 120° C. for 2 hours to obtain a polysilazane composite coating.

[0084] The preparation method of the two-dimensional composite material includes:

[0085] Dispersing 0.1 g of two-dimensional sheet material graphene oxide in 100 mL of deionized water under ultrasonic conditions to obtain a first dispersion;

[0086] The first dispersion liquid and 2.5 g of nanomaterial precursor Zn(CH3COO)2·2H2O are first mixed under stirring conditions to obtain a dispersion liquid;

[0087] The dispersion and NH3·H2O solution (wherein the molar ratio of hydroxide ions in the nanomaterial precursor Zn(CH3COO)2·2H2O and the NH3·H2O solution is 1:10) are mixed and first grown in situ at 180°C for 24 hours and then cooled to 25°C. The resulting mixed solution is washed with deionized water 6 times and then with anhydrous ethanol 4 times. The washed mixed solution is freeze-dried and then calcined at 450°C for 4 hours to obtain a two-dimensional composite material.

[0088] Example 4

[0089] Weigh 5 g of polyborosilazane, 1 g of chloroprene rubber and 1 g of 12-hydroxystearic acid, mix and disperse them in 10 g of propylene glycol methyl ether acetate to obtain a first mixed slurry; add 0.1 g of a two-dimensional composite material (graphene oxide (sheet diameter is 3000-5000 nm) and elemental zinc (granular morphology, particle size is 60 nm) in a mass ratio of 1:1) to the first mixed slurry, stir well to obtain a second mixed slurry; add 0.02 g of Mayer HY-5030, 0.02 g of Enze 2513, 0.02 g of Mayer HY-62S and 0.02 g of Lida LD-1291S to the second mixed slurry, continue stirring for 10 minutes to obtain a polysilazane composite coating.

[0090] The metal substrate was sandblasted to achieve a surface roughness of 2.6 μm.

[0091] The polysilazane composite coating was uniformly sprayed on the surface of the metal substrate, and then surface dried for 6 hours at room temperature, and then cured at 120° C. for 2 hours to obtain a polysilazane composite coating layer.

[0092] The method for preparing the two-dimensional composite material comprises:

[0093] Dispersing 0.1 g of two-dimensional sheet material graphene oxide in 100 mL of deionized water under ultrasonic conditions to obtain a first dispersion;

[0094] The first dispersion liquid and 2.5 g of nano metal precursor (zinc chloride) are first mixed under stirring conditions to obtain a dispersion liquid;

[0095] The dispersion, ethylene glycol (50 mL), sodium acetate (11.8 g) and polyethylene glycol (50 mL) were mixed at 200 °C for a second in situ growth for 2 h, then cooled to 25 °C and filtered. The filtered solid was washed with deionized water 7 times and anhydrous ethanol 5 times. The washed solid was dried under nitrogen protection at 60 °C for 4 h to obtain a two-dimensional composite material.

[0096] Example 5

[0097] The difference from Example 3 is that the toughening agent styrene butadiene rubber in Example 3 is replaced by a toughening agent terminal hydroxyl polybutadiene rubber.

[0098] Comparative Example 1

[0099] The difference from Example 3 is that the toughening agent styrene-butadiene rubber in Example 3 is omitted.

[0100] Comparative Example 2

[0101] The difference from Example 1 is that the lubricants 12-hydroxystearic acid, trimethylolpropane oleate and glycerol trihydroxystearate in Example 1 are omitted.

[0102] Comparative Example 3

[0103] The difference from Example 1 is that the two-dimensional composite material in Example 1 is omitted.

[0104] Test Case

[0105] The performance of the polysilazane composite coating layers obtained in Examples 1 to 4 and Comparative Examples 1 to 4 was tested.

[0106] Thickness test: The coating thickness is tested using a thickness gauge according to the method in GB1764-79 (89).

[0107] Adhesion performance test: Adhesion test is carried out according to the cross-cut test method of GB / T 9286-1998.

[0108] The tribological performance test was conducted under the following conditions: load 1N, dual Φ=6mm Si3N4 ball, reciprocating mode frequency 1Hz, and test time 30min.

[0109] Wear rate test: Use a surface profiler to measure the wear amount, and then use the wear rate calculation formula (Where ΔV is the wear volume change, mm 3 ; S is the stroke, m; P is the load size, N) for calculation.

[0110] Toughness test: The flexibility of the coating is measured in accordance with the national standard GB / T 1731-1993. A shaft with a curvature radius of 1 mm is used to bend the coating 180° against the shaft to observe whether the coating surface is cracked or peeled off.

[0111] The test results are shown in Table 1.

[0112] Table 1 Performance parameters of polysilazane composite coatings obtained in Examples and Comparative Examples

[0113]

[0114] It can be seen from Table 1 that the composite coating system described in the present invention uses an elastic polymer as a toughening agent to have a toughening effect on polysilazane, thereby solving the problem of high brittleness of polysilazane; the use of a toughening agent can also reduce the internal stress of the polysilazane composite coating formed by the polysilazane composite coating, avoid cracking of the polysilazane composite coating, and thus enable the polysilazane composite coating to be thickly coated. Using a hydroxyl-containing substance as a lubricant can improve the lubricity and wear resistance of the polysilazane composite coating. The use of a two-dimensional composite material can also significantly improve the wear resistance and corrosion resistance of the polysilazane composite coating, while also giving the polysilazane composite coating a lubrication function.

[0115] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A polysilazane composite coating, characterized in that: By mass, it includes the following components: 5-15 parts of polysilazane, 1-5 parts of toughening agent, 1-5 parts of lubricant, 0.05-0.5 parts of two-dimensional composite filler, 10-30 parts of dispersion medium, 0.01-0.1 parts of auxiliary agent; The toughening agent is an elastic polymer; The lubricant is an alcohol substance and / or an ester substance.

2. The polysilazane composite coating according to claim 1, characterized in that: The polysilazane includes one or more of vinyl polysilazane, methyl polysilazane, polyurea silazane, fluorine-modified polysilazane, polyborosilazane and perhydropolysilazane.

3. The polysilazane composite coating according to claim 1, characterized in that: The elastic polymer includes one or more of nitrile rubber, hydroxyl-terminated polybutadiene rubber, chloroprene rubber, natural rubber, styrene-butadiene rubber, butadiene rubber, hydrogenated nitrile rubber, butyl rubber, thermoplastic polyurethane elastomer, acrylic rubber and isoprene rubber.

4. The polysilazane composite coating according to claim 1, characterized in that: The alcohol substance includes one or more of monohydric alcohol, dihydric alcohol, trihydric alcohol and tetrahydric alcohol, the monohydric alcohol includes one or more of dodecanol, 12-hydroxystearic acid, isomeric tridecanol, tetradecanol, hexadecanol and octadecyl alcohol, the dihydric alcohol includes one or more of ethylene glycol, propylene glycol, pentanediol, hexanediol and cis-2-butene-1,4-diol, the trihydric alcohol includes one or more of glycerol, butanetriol and estriol, and the tetrahydric alcohol includes pentaerythritol; the ester substance includes trimethylolpropane oleate and / or glyceryl trihydroxystearate.

5. The polysilazane composite coating according to claim 1, characterized in that: The two-dimensional composite filler comprises a two-dimensional sheet material and a nanomaterial attached to the surface of the two-dimensional sheet material; the nanomaterial comprises a metal oxide nanomaterial or a nanometal; The two-dimensional sheet material includes one or more of graphene oxide, molybdenum disulfide, hexagonal boron nitride, mica sheet, MXene material and clay; The metal oxide nanomaterial includes magnesium oxide, calcium oxide, aluminum oxide or zinc oxide; The nano metal includes iron, copper, magnesium, cobalt or zinc; The mass ratio of the two-dimensional sheet material to the nano material is 1:1 to 10:

1.

6. The polysilazane composite coating according to claim 1, characterized in that: The dispersion medium includes one or more of n-butyl ether, n-hexane, propylene glycol methyl ether acetate, acetone, dichloromethane, ethyl acetate, tetrahydrofuran, 1,1,2-trichlorotrifluoroethane, perfluorohexane, perfluorocyclohexane, perfluorotoluene, perfluoroheptane and perfluorotrialkylamine.

7. The polysilazane composite coating according to claim 1, characterized in that: The auxiliary agent includes a wetting and dispersing agent, a defoaming agent, a leveling agent and a dustproof agent; the mass ratio of the wetting and dispersing agent, the defoaming agent, the leveling agent and the dustproof agent is (0.9-1.1): (1.0-1.2): (0.8-1.0): (0.8-1.0).

8. The method for preparing the polysilazane composite coating according to any one of claims 1 to 7, characterized in that: The following steps are involved: The polysilazane, the toughening agent, the lubricant and the dispersion medium are first mixed to obtain a first mixed slurry; The first mixed slurry and the two-dimensional composite filler are mixed for a second time to obtain a second mixed slurry; The second mixed slurry and the auxiliary agent are mixed for the third time to obtain the polysilazane composite coating.

9. Use of the polysilazane composite coating according to any one of claims 1 to 7 or the polysilazane composite coating prepared by the preparation method according to claim 8 in the protection of metal substrates.

10. The use according to claim 9, characterized in that: The coating thickness of the polysilazane composite coating is 5 to 100 μm.

Citation Information

Patent Citations

  • Low-surface-energy multifunctional lubricating protective paint based on polysilazane as well as coating and application of low-surface-energy multifunctional lubricating protective paint

    CN117535009A

  • Two-dimensional composite material, preparation method of two-dimensional composite material, barrier coating and application of barrier coating

    CN117777780A

Cited By

  • Corrosion-resistant metal surface composite coating material and preparation method thereof

    CN119615316A

  • Aerospace bearing wear-resistant coating based on polysilazane and preparation method thereof

    CN120272107A

  • Normal-temperature self-curing polysilazane coating and preparation method thereof

    CN122188523A

  • A room-temperature self-curing polysilazane coating and its preparation method

    CN122188523B